Expanded porphyrins and their evaluation as anion chemosensors - Figueira, Flávio Alberto da Silva (2018)
Expanded porphyrins are synthetic analogues of porphyrins, differing from the last ones and other naturally occurring tetrapyrrolic macrocycles by containing a larger central core, with a minimum of 17 atoms, while retaining the extended conjugation features that are a tremendous feature of these biological pigments. The core expansion results in various systems with novel spectral and electronic features, often uniques. Most of these systems can also coordinate cations and/or anions, and in some cases they can bind more than one of these species. In many cases, these molecules display structural features, such as non-planar structures, that have no antecedents in the chemistry of porphyrins or related macrocyclic compounds. This work will discuss several synthetic approaches for the synthesis of expanded porphyrins, namely the construction of new building blocks by Michael addition, as well as potential synthetic routes towards expanded porphyrins. The synthesis of smaller oligopyrrolic compounds namely, bipyrroles and dipyrromethanes, not only were developed for the synthesis of expanded porphyrins as they were also used in Knoevenagel condensations furnishing chromogenic compounds able to recognize different anions in solution. Also, an approach to the synthesis of novel expanded porphyrins namely sapphyrins has been done by aza-Michael additions. Several synthetic routes towards the synthesis of pyridyl and pyridinium N-Fused pentaphyrins and hexaphyrins have been explored in order to achieve compounds with potential applications in catalysis and PDI, respectively. Studies on the synthesis of compounds with potential anion binding properties, led to the structural characterization and NMR anion binding studies of [28]hexaphyrins functionalized with several diamines in the para position of their pentafluorophenyl groups. These compounds allow NH hydrogen bond interactions with various anions. All synthesized compounds were fully characterized by modern spectroscopic techniques.